The Effect Of Giving Torbangun Leaves (Coleus Amboinicus Lour) On Increasing Breast Milk Production - Muliatul Jannah; Arum Meiranny; Nicky Febriani Putri Nurzaen (Alma Ata University Press, 2020)
Breast milk is the best natural nutrition for babies because it contains the energy and substance needs needed for the first six months of a baby's life. Breast milk contains a lot of substances on children's survival, growth and development. Despite the many benefits of breastfeeding, the coverage of exclusive breastfeeding is still low. One of the most common factors associated with the failure to practice exclusive breastfeeding is the breast milk has not come out in the first week after delivery and the mother's view that her milk production is not sufficient. Breast milk production is influenced by two hormones, namely prolactin and oxytocin, also lactogagum in food which can increase milk production. Therefore, the leaves are suitable for increasing milk production because they contain lactogagum. To examine the effect of giving torbangun leaves on increasing breast milk production. Literature from within the country and abroad can be traced through electronic media with keyword guidance. There are 4 selected articles, each representing an effect of torbangun leaves (Coleus amboinicus Lour) on increasing breast milk production and providing varied information. There was an increase in the production of breastmilk in the giving of torbangun leaves to the respondents with the same treatment.Based on the analysis that has been done, the use of torbangun leaves is effective to increase milk production.